Area deprivation and premature cardiovascular mortality: a nationwide population-based study in South Korea - Hyeon Chang Kim; Hokyou Lee; Eunji Kim; Donald Lloyd-Jones; Young Gyu Ko; Byoung Gwon Kim (BMJ Public Health)
Background Regional disparities in cardiovascular disease (CVD) burden exist. The effect of area deprivation, one of the possible explanations, still needs to be fully understood. This population-based study investigated the association between Area Deprivation Index (ADI) and CVD-related premature death.Methods ADI was derived from 10 socioeconomic indicators in 250 South Korean municipalities using the 2020 Population and Housing Census data. Mortality rates for CVD and its subtypes, namely ischaemic heart diseases, other heart diseases and cerebrovascular diseases, in adults under 65 years were directly standardised by sex and age, referencing the total population structure. Municipalities were categorised by urbanicity, and adjustments for the number of hospitals and geographical area size were made using log-linear regression models.Results The most deprived municipalities showed 41.6% excess mortality for CVD, 30.3% for ischaemic heart diseases, 60.7% for other heart diseases and 36.9% for cerebrovascular diseases compared with the least deprived municipalities. Even after adjusting for the number of hospitals per unit area, the association between ADI and premature CVD death was more significant in metropolitan areas than in other provinces. For each incremental increase in the continuous ADI, the adjusted mortality rate ratios were observed as 1.031 (95% CI, 1.020 to 1.043) in metropolitan areas and 1.009 (95% CI, 1.000 to 1.019) in other provinces. Additional multilevel analyses showed consistent findings of a higher risk in deprived areas.Conclusion This study highlights a higher risk of premature cardiovascular death in socioeconomically disadvantaged areas. CVD prevention strategies should reflect regional characteristics and focus on reducing the burden in deprived metropolitan areas.